Association of Maternal Age, Parity, and Early Initiation of Breastfeeding with Breast Engorgement Among Postpartum Women at Bayiku Lactation Clinic, Sleman, Yogyakarta - Mona Jatilia; Luluk Rosida; Fathiyatur Rohmah (Althar Cendikia Education, 2026)
Breast engorgement is a common lactation problem in postpartum mothers and can hinder the breastfeeding process and increase the risk of exclusive breastfeeding failure. Factors associated with breast engorgement include maternal age, parity, and implementation of Early Breastfeeding Initiation. The study aims to determine the correlation between maternal age, parity, and implementation of Early Breastfeeding Initiation with the incidence of breast engorgement in postpartum mothers at Bayiku Lactation Clinic, Sleman, Yogyakarta. Quantitative research with descriptive analytical design using a cross-sectional approach was employed as the research method. A sample of 33 postpartum mothers was selected using an accidental sampling technique. Data were collected through interviews using factual questionnaires and analyzed using the Spearman Rank test. A total of 42.4% of respondents experienced breast engorgement. There was a significant correlation between maternal age and the incidence of breast engorgement (p=0.038; r=-0.363), parity (p=0.009; r=0.448), and Early Breastfeeding Initiation (p=0.000; r=0.694). The Early Breastfeeding Initiation variable showed the strongest correlation with the incidence of breast milk engorgement. There is a significant correlation between maternal age, parity, and implementation of Early Breastfeeding Initiation with the incidence of breast milk engorgement in postpartum mothers, and Early Breastfeeding Initiation becomes the factor with the strongest correlation. Optimizing Early Breastfeeding Initiation implementation and lactation education is recommended as an effort to prevent breast milk engorgement.